Institutional arrangements between sugarcane growers and millers in Uganda and implications for grower productivity and profitability - Mbowa, Swaibu; Guloba, Madina M.; Mather, David L.; Nakazi, Florence; Bryan, Elizabeth; Nakkazi, Sheila (Michigan State University Press, 2023)
This study investigates sugarcane grower productivity and profitability in Uganda and whether and how they are influenced by institutional arrangements between sugarcane growers and millers. Analysis is based on primary data collected from 983 sugarcane growing farm households in the three main sugarcane-producing regions of Busoga, Buganda, and Bunyoro. The study finds evidence that use of key quality inputs and crop and soil management practices are associated with higher farmer cane yield. There is also a clear trade-off (an inverse relationship) between the level of competition between large and small cane mills in a region and the level of grower-miller coordination of market assurance and input access, as embodied by institutional arrangements between growers and millers. Better grower-miller coordination was associated with better grower access to a market for mature cane and access to key inputs and services such fresh, quality cane seedlings and cane-specific extension. In turn, better market access and higher yields are associated with higher farmer cane profits per acre. Revision of the existing policy framework and enabling environment of cane production and processing in Uganda is needed to resolve several contentious policy issues and provide public sector oversight of grower-miller relations and better coordination of the national supply of and demand for cane. Success of this policy reform is vital for the cane industry to remain both financially sustainable and inclusive.